Tumor-Derived Extracellular Vesicles Regulate Cancer Progression in the Tumor Microenvironment - Bao, Qianqian; Huang, Qianqian; Chen, Yunna; Wang, Qiang; Sang, Ran; Wang, Lei; Xie, Ying; Chen, Weidong (Frontiers in Molecular Biosciences, 2022)
Extracellular vesicles (EVs) are nanosized particles released by numerous kinds of cells, which are now increasingly considered as essential vehicles of cell-to-cell communication and biomarkers in disease diagnosis and treatment. They contain a variety of biomolecular components, including lipids, proteins and nucleic acids. These functional molecules can be transmitted between tumor cells and other stromal cells such as endothelial cells, fibroblasts and immune cells utilizing EVs. As a result, tumor-derived EVs can deliver molecules to remodel the tumor microenvironment, thereby influencing cancer progression. On the one hand, tumor-derived EVs reprogram functions of endothelial cells, promote cancer-associated fibroblasts transformation, induce resistance to therapy and inhibit the immune response to form a pro-tumorigenic environment. On the other hand, tumor-derived EVs stimulate the immune response to create an anti-tumoral environment. This article focuses on presenting a comprehensive and critical overview of the potential role of tumor-derived EVs-mediated communication in the tumor microenvironment.